Penile length and cord total and free testosterone in full term male Egyptian neonates - Maha Hassan Mohamed; Rania Mohamed Abdou; Mohamed Tareef Hamza; Mai Mohamed Saber Hussein (SpringerOpen, 2015)
Background: It is inappropriate to use universal reference values to interpret stretched penile length measurements and testosterone concentrations in newborns with variable ethnic backgrounds. Objective: To establish normal reference values for stretched penile length, free and total testosterone concentrations in fullterm Egyptian newborn and to correlate them with anthropometric parameters. Methods: 180 fullterm healthy newborn boys to uncomplicated pregnancies and deliveries were enrolled. Penile length, weight, length, occipitofrontal circumference were measured within 24 h of birth. Total and free testosterone concentrations were assayed. Results: The mean penile length was 3.14 ± 0.38 cm, the mean free testosterone was 13.76 ± 8.67 pg/ml, mean total testosterone was 1.98 ± 1.35 ng/ml. Penile length correlated positively to birth weight, to crown heel length and to penile length/crown heel length ratio. Penile length correlated positively to free and total testosterone. Total testosterone level correlated positively to crown heel length and to free testosterone. Conclusion: Our study is a step toward achieving accurate reference charts for Egyptian male newborns. A multicenter, larger scale study is needed to establish Egyptian norms.